A novel route to get functionality in nanoelectronics: Controlling the charge transport by the subtle impact of the coverage of self-assembled monolayers on the conformation of floppy molecules adsorbed on metallic electrodes - Bâldea, Ioan (Applied surface science, 2019)
Molecules at interfaces can exhibit a behavior that is very different from that in bulk phases. In this paper we will analyze one important factor that makes the difference between these two situations. Unlike in bulk situations—which are characterized by a practically constant density and a given type of crystal structure—molecules in a self-assembled monolayer (SAM) adsorbed on a substrate electrode are characterized by a density (coverage) and an ordering that can be widely tuned. The theoretical results presented in this paper indicate that tuning the coverage of SAMs consisting of floppy molecules may have a strong impact on the molecular conformation. Therefore, it may represent a route to achieve interface-driven control over the charge transfer/transport at molecular scale. Specifically, we consider three floppy molecular species—H-(C6H4)2-SH (biphenylmonothiol), HS-(C6H4)2-SH (4,4′-dithiol-1,1′-biphenyl), and NC5H4-C6H4-SH (4-(4-pyridinyl) benzenethiol)—consisting of two benzene or benzene-based rings that can easily rotate relative to each other. Our calculations reveal that, by varying the SAM coverage, the torsional angle can be varied by a factor of two. This reflects itself in a change of conductance over one order of magnitude, a fact that can be exploited in designing molecular switches.